INTERNATIONAL COOPERATION DESPITE COLD WAR? APPROACHES BETWEEN THE WOMEN’S INTERNATIONAL DEMOCRATIC FEDERATION THE WOMEN’S INTERNATIONAL LEAGUE FOR PEACE AND FREEDOM (1945-1963) - Nunes, Guilherme Machado [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2024)
After the Second World War, international women’s organizations that already existed before the War, such as the Women’s International League for Peace and Freedom (WILPF), began to coexist with new actors. One of them argues that women’s issues could not be separated from themes such as colonialism, imperialism and protection of motherhood and childhood: the Women’s International Democratic Federation (WIDF). Although there were moments of conflicts and disputes typical of the period, the main goal of this article is to explore the attempt at cooperation, as well as the circulation of these women through countries and organizations that had the Cold War not only as a limiter, but also a field that enabled new channels and ways of communication. In this process, women in Latin America played an important role in trying to overcome the Cold War obstacles, especially through initiatives related to motherhood in the 1950s.
COOPERAÇÃO INTERNACIONAL APESAR DA GUERRA FRIA? APROXIMAÇÕES ENTRE A FEDERAÇÃO DEMOCRÁTICA INTERNACIONAL DE MULHERES E A LIGA INTERNACIONAL DE MULHERES PRÓ-PAZ E LIBERDADE (1945-1963)1
Keywords: Cold War; feminism; WIDF; WILPF; women’s history